2018
DOI: 10.11646/phytotaxa.362.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Phylogeny of the Ficus auriculata Complex (Moraceae)

Abstract: The closely related species of the genus Ficus with continuous variation have been confusing taxonomists, co-evolutionary researchers, and other related scientists. The boundary between species in the complex of F. auriculata, F. oligodon, F. hainanensis, F. beipeiensis, and F. variegata is still unclear. To clarify this problem, the nuclear loci ITS and G3pdh; chloroplast loci trnH-psbA, trnL-trnF, trnS-trnG, and psbK-psbI; and 15 pairs of SSR markers were used to reconstruct the phylogenetic relationship and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 1 publication
0
13
0
Order By: Relevance
“…Distribution: The species native to India (Himalayas), Bhutan, Nepal, Sikkim, Myanmar, Thailand, and Southern China (Berg & Corner 2005;Lim 2012). In the Malesia Region, F. auriculata was only recorded from Selangor and Pahang, Malaysia (Corner 1965;Berg & Corner 2005;Zhang et al 2018). However, in this study, this species has been planted in Java and Madura.…”
Section: Taxonomic Treatmentmentioning
confidence: 69%
“…Distribution: The species native to India (Himalayas), Bhutan, Nepal, Sikkim, Myanmar, Thailand, and Southern China (Berg & Corner 2005;Lim 2012). In the Malesia Region, F. auriculata was only recorded from Selangor and Pahang, Malaysia (Corner 1965;Berg & Corner 2005;Zhang et al 2018). However, in this study, this species has been planted in Java and Madura.…”
Section: Taxonomic Treatmentmentioning
confidence: 69%
“…Roxburgh fig, F. oligodon , and F. hainanensis were also the same ethnospecies among Danu, Pa-O, and Shan. Molecular phylogeny research studies have revealed the same three forms as one species [ 45 ], and the three were once considered synonyms of roxburgh fig [ 38 ]. It may be worthwhile to study more of the similarities among local names and molecular phylogeny.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the positive effect of Aristolone content in F. auriculata affected proliferation supported by previous studies. as a single species (Zhang, 2018). It uses for food and has socioeconomic importance, the near-ripe peeled or unpeeled fruits and young leaves of F. auriculata were sold such as in the north and central Vietnam (Mon, 2020).…”
Section: Article Historymentioning
confidence: 99%